The Berlin Stock Exchange in Imperial Germany: A Market for New Technology? - Lehmann-Hasemeyer, Sibylle; Streb, Jochen (American Economic Review, 2016)
Analyzing 474 cases of firms going public in the German capital between 1892 and 1913, we show that innovative firms could rely on the Berlin stock market as a source of financing. Our data also reveal that initial public offerings (IPO) of innovative firms were characterized by particularly low underpricing, comparatively high first trading prices, and no long-run underperformance. We interpret these empirical results as evidence for the surprising fact that in the period of the Second Industrial Revolution the Berlin stock exchange was already a well-functioning market for new technology. (JEL G14, N23)